2016
DOI: 10.1111/1471-0528.14055
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of cancer antigen 125 for endometriosis: a systematic review and meta‐analysis

Abstract: Blood test CA 125: a rule-in test for the diagnosis of women presenting with symptoms of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 65 publications
3
72
0
1
Order By: Relevance
“…CA 125 is particularly useful in diagnosing and detecting the recurrence of gynecologic tumors (18,19); this marker is also observed in patients with lung, breast and gastrointestinal tract cancer. Evaluated CA 19-9 is often found in patients with gastrointestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA 125 is particularly useful in diagnosing and detecting the recurrence of gynecologic tumors (18,19); this marker is also observed in patients with lung, breast and gastrointestinal tract cancer. Evaluated CA 19-9 is often found in patients with gastrointestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of one published meta-analysis, including 21 studies with a total of 2,861 cases, were similar to our study and showed that the sensitivity and specificity of CA 15-3 in the diagnosis of MPE were 0.58 (95% CI: 0.56-0.61) and 0.91 (95% CI, 0.90-0.93) (17). However, we suggest that CA 15-3 alone is not recommended due to its limited sensitivity.CA 125 is particularly useful in diagnosing and detecting the recurrence of gynecologic tumors (18,19); this marker is also observed in patients with lung, breast and gastrointestinal tract cancer. Evaluated CA 19-9 is often found in patients with gastrointestinal tumors.…”
mentioning
confidence: 99%
“…Serum cancer antigen 125 (CA‐125), also known as mucin 16 (MUC16) is a protein that belongs to the mucin family of glycoproteins and is expressed by epithelia as a response to infectious agents and foreign particles . As a biomarker it is mainly used to diagnose endometriosis and ovarian cancer as well as during the follow‐up period of patients treated for ovarian cancer . Despite its relatively high specificity, its sensitivity remains low and, thus, a negative test is unable to rule out the presence of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…7 As a biomarker it is mainly used to diagnose endometriosis and ovarian cancer as well as during the follow-up period of patients treated for ovarian cancer. 8,9 Despite its relatively high specificity, its sensitivity remains low and, thus, a negative test is unable to rule out the presence of these diseases. A recent metaanalysis in the field of heart failure implied that serum CA-125 may be used as a biomarker that could help diagnose, stratify and predict Abstract Background: Preeclampsia is a leading cause of perinatal morbidity, although an optimal screening model is still under investigation.…”
mentioning
confidence: 99%
“…Research has been carried out investigating biomarkers in diagnosing endometriosis, in particular CA 125. While there is some diagnostic use as a ‘rule in’ test, its sensitivity remains poor and performs poorly as a ‘rule out’ test with almost half of patients with endometriosis having a negative test 7. A validated assessment tool exists based purely off examination and ultrasound findings, however, this only lends itself to ovarian endometriosis 8.…”
Section: Discussionmentioning
confidence: 99%